Time-Dependent Effect of Chitosan Nanoparticles as Final Irrigation on the Apical Sealing Ability and Push-Out Bond Strength of Root Canal Obturation - Diatri Nari Ratih; Nikita Ika Sari; Pribadi Santosa; Nofa Mardia Ningsih Kaswati (Hindawi Limited, 2020)
Background/Objectives. Root canal irrigation is a crucial stage during root canal treatment since it can affect the root canal obturation; as a result, the success of root canal treatment can be achieved. The objective of this study is to evaluate the effect of 0.5% chitosan nanoparticles as a final irrigation solution with different application times on the apical sealing ability and the bond strength of root canal obturation. Materials and Methods. Fifty-six premolars were used in this study and divided by two evaluations: 28 teeth for apical sealing ability and 28 others for bond strength. Each study was assigned randomly into two groups of fourteen teeth: Group-1, final irrigation with 17% EDTA; Group-2, with 0.5% chitosan nanoparticles. Each group was further divided into two groups of 7 each: Group-A, final irrigation was applied for 1 minute; Group-B, for 3 minutes. All teeth were obturated with epoxy resin-based sealer and gutta-percha. In the apical sealing ability study, the obturated teeth were immersed in 2% methylene blue and observed under a stereomicroscope (8x magnification). In the bond strength study, the teeth were tested using the push-out technique and observed under a stereomicroscope (40x magnification) to determine the failure type. Data from each evaluation were analysed with two-way ANOVA followed by the LSD test. Results. Final irrigation using 0.5% chitosan nanoparticles produced the same apical sealing ability and bond strength as 17% EDTA (p>0.05). A significant difference occurred between application times (p<0.05). The failure type was observed predominantly as cohesive, and the least was adhesive. Conclusion. Regardless of the final irrigation solution used, 3-minute application time produced greater apical sealing ability and push-out bond strength than 1-minute application time.